2016
DOI: 10.18805/ijar.10976
|View full text |Cite
|
Sign up to set email alerts
|

Protective role and antioxidant activity of arabic gum againsttrichloroacetate-induced toxicity in liver of male rats

Abstract: Investigation of functional hepatoprotective components from plants origin is a new model for drug evolution. The study examined the protective effects of Arabic gum (AG) induction on liver serum markers, antioxidant enzymes and lipid peroxidation in liver tissue against trichloroacetate (TCA) induced hepatotoxicity in male albino rats. Also, the chemical constituents and antioxidant assay of aqueous extract of AG was determined. TCA at the dose of 50 mg/kg for 2 months produced hepatotoxicity as examined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
(25 reference statements)
5
22
0
Order By: Relevance
“…ROS, which is increasingly produced by reperfusion and is therefore called a reperfusion mediator, leads to the oxidation of cell membrane lipids. MDA, which results from the oxidation of lipids, increases the severity of cell damage and causes cell death (Ayaz et al, 2017;Yapca et al, 2013). In the current study, I/R resulted in an increase in MDA levels in ovarian tissue (p < 0.0001).…”
Section: Resultssupporting
confidence: 50%
“…ROS, which is increasingly produced by reperfusion and is therefore called a reperfusion mediator, leads to the oxidation of cell membrane lipids. MDA, which results from the oxidation of lipids, increases the severity of cell damage and causes cell death (Ayaz et al, 2017;Yapca et al, 2013). In the current study, I/R resulted in an increase in MDA levels in ovarian tissue (p < 0.0001).…”
Section: Resultssupporting
confidence: 50%
“…Treatment of male rats with Trichloroacetate decreased the level of hepatic superoxide dismutase and catalase and increased the concentration of MDA. The trichloroactate toxicity was reversed by gum Arabic and peppermint oil [7,20].…”
Section: Effect Of Gum Arabic On Liver Function and Antioxidant Enzymmentioning
confidence: 99%
“…Some studies showed the effectiveness of gum Arabic as antioxidant material in food preservation [5,6] and in animals and humans through increasing the concentration of antioxidant enzymes and decreasing the oxidizing molecules in different organs [7,8]. With regard to the side effects of gum Arabic, some studies have reported the uncoupling of oxidative phosphorylation in the heart and liver [9], allergy and hypersensitivity [10,11].The aim of this article was to investigate the effect of gum Arabic on the liver function and antioxidant activity of Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…They are also sensitive indicators of liver injury (Molander et al, 1955;Ozer et al, 2008;Ayaz et al,2017). Injury to the hepatocytes alters their transport function and membrane permeability, leading to leakage of enzymes from the cells (Zimmerman and Seeff, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, conventional or synthetic drugs used in the treatment of liver diseases are inadequate and sometimes can have serious side effects (Kala et al, 2013). Many traditional remedies employ herbal drugs for the treatment of liver ailments (Mohan et al, 2005;Ayaz et al, 2017). Brown seaweed has been used as foodstuff in the Asian diet for centuries.…”
Section: Introductionmentioning
confidence: 99%